ANALISIS KEMAMPUAN KONEKSI MATEMATIKA PADA MATERI TRANSFORMASI SISWA KELAS XI SMK NEGERI 1 LAHUSA TAHUN PEMBELAJARAN 2020/2021 - Syukur Hati Ziliwu(1); Rohpinus Sarumaha(2); Darmawan Harefa(3) (Afore : Jurnal Pendidikan Matematika, 2022)
This research is motivated by the low ability of students’ mathematical connection in the transformation material. This study aims to describe students’ mathematical connection abilities, especially in the transformation material. This research uses qualitative research with descriptive research approach. The informants of this study were students of class XI SMK Negeri 1 Lahusa totaling 20 students. The data were analyzed by the steps of data collection, data reduction, data presentation, and drawing conclusions. The research instrument used was a test of students’ mathematical connection abilities with interviews. Based on the results of the research and discussion, the researchers concluded that class XI sudents of SMK Negeri 1 Lahusa have mathematical connection abilities in the low category. The findings of the study showed that: students did not understand the concept of transformation, students did not understand the relationship between the concept transformation and other mathematical topics, such as linear equations of one variable and staright line equations, students were unable to find the relationship between transformation completion procedures and other mathematical materials, and students were unable to apply concepts in everyday life and in other fields of science. This is because students do not understand the problem, students are confused in choosing the right completion procedure, and the lack of accuracy of students in performing mathematical calculation operations so that calculation errors often occur. Through this research, it is suggested that students mathematical connection abilities be further improved by in creasing regular practice on questions related to mathematical connections